SOME NEW REMAINS OF HIPPARION FROM THE DHOK PATHAN TYPE LOCALITY, PAKISTAN - M. Iqbal; A. Liaqat; M. A. Khan; M. Akhtar (Journal of Animal and Plant Sciences, 2009)
Dental material attributed to H. antilopinum from the Upper Miocene of the Dhok Pathan village near Dhok Kundrali is described and discussed. Preserved features of the dentition permit to assign H. antilopinum for the specimens. H. antilopinum is found abundantly in the Middle Siwaliks and considered as one of the faunal members of the Siwalik Late Miocene sediments.
Keywords: Hipparion; Dhok Pathan; Middle Siwaliks; Late Miocene; H. antilopinum